Structural style and neotectonic activity along the Harz Boundary Fault, northern German: a multimethod approach integrating geophysics, outcrop data and numerical simulations - Müller, Katharina; Polom, Ulrich; Winsemann, Jutta; Steffen, Holger; Tsukamoto, Sumiko; Günther, Thomas; Igel, Jan; Spies, Thomas; Lege, Thomas; Frechen, Manfred; Franzke, Hans‑Joachim; Brandes, Christian (Berlin, 2020)
We present new evidence for neotectonic activity along the Harz Boundary Fault, a Cretaceous reverse fault that represents a key structure in northern Germany. For the fault analysis, we use a multimethod approach, integrating outcrop data, luminescene dating, shear wave seismics, electrical resistivity tomography (ERT) and numerical simulations. A recent sinkhole at the SSW-ward dipping and WNW–ESE striking Harz Boundary Fault exposes a NNE-ward dipping and WNW–ESE striking planar fault surface that cuts through unconsolidated debris-flow deposits thus pointing to young Lateglacial tectonic activity. The fault shows a polyphase evolution with initial normal fault movement and a later reactivation as an oblique fault with reverse and strike-slip components. A shear wave seismic profile was acquired to analyse the geometry of the fault and show that the Harz Boundary Fault is steeply dipping and likely has branches. Partly, these branches propagate into overlying alluvial-fan deposits that are probably Pleniglacial to Lateglacial in age. The outcrop data in combination with the seismic data give evidence for a splay fault system with steep back-thrusts. One of these back-thrusts is most likely the NNE-ward dipping fault that is exposed in the sinkhole. The lateral extent of the fault was mapped with electrical resistivity tomography (ERT) profiles. The timing of fault movement was estimated based on optically stimulated luminescence dating of the faulted debris-flow deposits using both quartz and feldspar minerals. Consistent feldspar and quartz ages indicate a good bleaching of the sediment prior to deposition. The results imply fault movements post-dating ~ 15 ka. Numerical simulations of glacio isostatic adjustment (GIA)-related changes in the Coulomb failure stress regime at the Harz Boundary Fault underpin the assumption that the fault was reactivated during the Lateglacial due to stress changes induced by the decay of the Late Pleistocene (Weichselian) Fennoscandian ice sheet. © 2020, The Author(s). ...